A Structural Analysis of the Chinese Patriarchal Family Business Model: What Happens in the Corridors of the Shrine? - Kerbouche, Mohammed; Bouguesri, Imene (Economics and Business, 2020)
The family business features a replica of the family model, carrying the DNA of its structural foundational principles that sow the seeds of the vision of its creator (the family head). They are nonetheless bound by several external factors that determine their growth path. As the market is a highly unstable environment, resilience in strategy is demanded to maintain enterprise survival and improve its performance. In the present research, we attempt, firstly, to display the findings of an analysis of small and medium-size Chinese organisations that sketches their characteristics, including the following elements: the style of the leader, decision-making style, leadership style, organisation structure, supervision, variables related to the manager and organisation ownership. Secondly, we delineate the impact of the implementation of a set of strategy configurations on Chinese business effectiveness. The research findings reveal a considerable impact of the aforementioned variables on Chinese SME effectiveness; they reflect a strong presence of the produce or perish leadership style, a predictable characteristic of enterprises led by males (with an effect estimated with 0.48) combined with the entrepreneurial type of leader that entails a strict mode of management (centralization) and subsequently influences business effectiveness. All these characteristics confirm the replication of the family management style within SMEs.